Prevalance and Risk Factor of Hearing Loss in Type 2 Diabetes Mellitus at Priest Hospital - Chongsatja, Terapat (Journal of The Department of Medical Services, 2021)
Background : The hearing loss in type 2 diabetic mellitus (T2DM) are slowly progression, with do not affect to communication in daily activity. There are many risks that affect to hearing loss, e.g., age, gender, duration of diabetic mellitus, blood sugar level and body mass index (BMI).Objective : The purpose of this research was to study prevalence and risk factor of hearing loss in type 2 diabetes mellitus at Priest Hospital.Methods : The study design was retrospective cohort study. Forty-six patients, type 2 diabetes mellitus in diabetic mellitus clinic, were audiogram test. Information of patients were collected from medical records.Results : The prevalence of hearing loss was 82.60%. High frequency hearing loss was the most level of hearing loss, right ear was 43.50% and left ear was 45.70%. The factor of hearing loss in type 2 diabetes mellitus were age and the duration of diabetes mellitus, which were significant difference (p-value < 0.05). The average age of both-ears normal hearing was 46.63±9.94 years and hearing loss was 56.50±9.87 years. The average duration of diabetes mellitus of both-ears normal hearing was 2.79±1.39 years and hearing loss was 4.56±2.66 years.Conclusion : The high frequency hearing loss was the early level in the type 2 diabetes mellitus patients, which did not affect in communication of daily activity. Thus, suggestion is to have hearing screening in type 2 diabetes mellitus.